Consumo e rituais de despedida: processos de escolha e decisão de compra nas cerimônias fúnebres premiuns da cidade de São Paulo e região metropolitana - Santos, Lígia Prada (2019)
This study investigated how the processes of choice and decision of purchase in the funeral ceremonies happen. To understand consumption during a funeral ceremonial, it will be essential to analyze the weight and degree of importance of the mourner's emotion versus the cost-benefit factor. The objective was to investigate how, faced with so many options and novelties, in detriment of the very little time it takes to reflect and execute the purchase, the consumer absorbs the information and decides. Other factors such as the disclosure of funeral products and services and the approach of the agents responsible for the sale were investigated for a better understanding of the whole process. The theoretical foundations pass through Sociology, since the structure and functioning of the funeral market are a consequence of processes widely studied by Baudrillard (1995), Debord (2006), Bourdieu (2003), among others. On the contemporary condition of death, the authors Ariès (2003), Morin (1997) and Maranhão (1986) represent the choices made. The methodological approach adopted was the use of qualitative research, through semi-structured interviews, to capture in depth information from the interviewees, through the freedom proposed by the method. The research carried out interviews with two segments of subjects: the most common decision maker for the purchase of services and products (family close to the deceased) and undertakers of the funeral market: funeral directors and businessmen. The results show the mapping of information that guides the processes of choice and decision making, as well as the possibility of an in-depth knowledge of how this market, in a frank expansion, acts to impact and communicate with its consumers.